1991
DOI: 10.1267/ahc.24.257
|View full text |Cite
|
Sign up to set email alerts
|

Rapid recovery of leydig cell population in rar cryptorchid testes after ethanedime-thanesulfonate injury: Immuno-histochemical studies.

Abstract: Precursor cells in the rapid recovery of Leydig cells after depletion by ethanedimethanesulfonate (EDS) injury to bilateral abdominal testes were examined immunohistochemically 8, 11, and 14 days after an intraperitoneal injection of EDS, 75 mg/kg, 2 weeks after cryptorchidization.Compared with shamoperated rats, the repopulation of Leydig cells in cryptorchid rats was accelerated. Row-like arranged fusiform-shaped mesenchymal cells were found in peritubular regions of abdominal testes 14 days after EDS inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…It has been shown that myoid cells in the adult rat proliferate at a low rate (Teerds et al, 1989). However, the myoid cells surrounding damaged seminiferous tubules could undergo proliferation similar to that reported for the Leydig cells in cryptorchid rats subjected to treatment with ethane dimethane sulphonate (Kerr & Donachie, 1986;Sharpe et al, 1990;Naka et al, 1991).…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…It has been shown that myoid cells in the adult rat proliferate at a low rate (Teerds et al, 1989). However, the myoid cells surrounding damaged seminiferous tubules could undergo proliferation similar to that reported for the Leydig cells in cryptorchid rats subjected to treatment with ethane dimethane sulphonate (Kerr & Donachie, 1986;Sharpe et al, 1990;Naka et al, 1991).…”
Section: Introductionsupporting
confidence: 66%
“…Both testes were removed and fixed by immersion in methacarn for several minutes. The testicular capsule was then punctured with a thin needle to make small holes to improve infiltration of the fixative and avoid organ deformhtion (Naka et al, 1991). The testes were fixed further in methacarn for 10 h, and then cross-sectioned into 3 mm thick slices which were embedded in paraffin.…”
Section: Tissue Preparationmentioning
confidence: 99%
“…Animals were killed by exsanguination under ether anaesthesia. Both testes were removed and fixed by immersion in methacarn for several minutes; the testicular albuginea was then punctured with a thin needle to improve fixative infiltration and avoid organ deformation (Naka et a/., 1991). The testes were further fixed in methacarn for 10 h, and then cross-sectioned into 3-mm thick slices which were embedded in paraffin.…”
Section: Tissue Preparationmentioning
confidence: 99%